Upscaling non-residential bio-based circular construction in the United Kingdom. Issue 1 (October 2021) - Dams, B; Maskell, D; Shea, A; Allen, S; Cascione, V; Walker, P; Emmitt, S
Abstract: Non-residential circular construction projects using bio-based materials have been realised in the United Kingdom. Case studies include the Adnams Distribution Centre, the University of East Anglia's Enterprise Centre and the British Science Museum's hempcrete storage facility. The bio-based buildings utilise the natural properties of bio-based materials to insulate and regulate internal environments, particularly with reducing fluctuations in temperature and relative humidity, which can be harmful to sensitive stored products and artefacts. Projects have been successful on both on environmental and physical performance levels; however, they have not led to a subsequent proliferation of non-residential large-scale circular projects within the UK using emerging bio-based materials. This study examines why and uses analysis based upon exclusive interviews with key figures associated with bio-based case studies. Challenges faced include the ability to upscale production by manufacturers of bio-based materials, problems surrounding initial costs, gaining accreditation for materials, the vested interests present in the construction industry and levels of knowledge among clients and construction professionals. Potential upscaling solutions identified include long-term financial savings on running costs and high staff productivity, policies regarding grants, incentives and planning applications and local economic regeneration.